Let's connect nature with hypothesis‐based experimentation and explore life in context. (13th December 2022) - Negin, Boaz; Aharoni, Asaph
SUMMARY: In a recent paper in Nature, Edith Heard from the European Molecular Biology Laboratory (EMBL) suggested that molecular biologists should 'reconnect with nature' by diversifying sampling locations. Although this approach has its own benefits, we suggest that advanced methods should rather be used to take hypothesis‐based experiments to nature, thereby supplying a much‐needed context for experimentation under controlled conditions. Following the CRISPR (clustered regularly interspaced short palindromic repeats) revolution, this approach has become accessible to many research groups. For the past several years we have developed the groundwork and initiated such experimentation. This included the assembly of a mobile laboratory on a four‐wheel drive truck and examining genome‐edited metabolic mutants in wild tree tobacco ( Nicotiana glauca ), grown in nature. Our findings included both targeted answers to focused questions, but also surprising results that could only be reached while working in natural settings. Significance Statement: With the fast development of accessible genome editing technologies and phenotyping platforms, scientists should use these cutting‐edge tools to carry out hypothesis‐based experiments in nature, thereby supplying a much needed context for experimentation under controlled conditions. Once embraced by the broad research community, this approach combining designed experimentation in natural settings and the ability to bring the lab to the trialing site is likely to expose scientists to different, yet unexplored spaces of biological knowledge.